2023
DOI: 10.3390/jcm12072710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reduction of Skin Hyperpigmentation Changes under the Influence of a Preparation Containing Kojic Acid Using Hyperspectral Imaging—Preliminary Study

Abstract: Aim: The aim of this study was to demonstrate the effects of using a preparation containing kojic acid on skin hyperpigmentation using hyperspectral imaging, which enables a quantitative assessment of the effect of the preparation used on the reduction of skin discoloration. Materials and methods: Preliminary studies were carried out on 12 patients with post-acne skin. A hyperspectral camera with a spectral range of 400–1000 nm was used to image skin hyperpigmentation before and after the application of 3% koj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This study showed that after microneedle mesotherapy with Vit. C improved skin lightening compared to kojic acid lightening, in which the contrast decreased and uniformity increased [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that after microneedle mesotherapy with Vit. C improved skin lightening compared to kojic acid lightening, in which the contrast decreased and uniformity increased [ 36 ].…”
Section: Discussionmentioning
confidence: 99%